1960
DOI: 10.1152/jappl.1960.15.6.1075
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation of lungs in infant and adult rats and its responses to hypoxia

Abstract: Do the controls of breathing differ with age? Pulmonary ventilation was measured by body plethysmograph and pressure transducer. After birth, breathing was irregular (pneumotaxic); steadiness from breath to breath was gained at 3 days; extraction of oxygen from the inspired air became more uniform after 10 days. In pO2 20–40 mm Hg only infants survived a half hour; ventilation did not usually increase, and often decreased. Hyperventilation even in 40 mm Hg was not sustained for many minutes in the newborn, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1960
1960
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Twenty-one of 27 species from five mammalian orders included in the study by Frappell et al (1992) showed large ( > 20%) reductions in 1902 and corresponding reductions in TB upon exposure to 10% Oz. These data, together with data for five other species of rodents (Morrison and Rosenmann 1975), guinea pigs (Hill 1959), and rats (Adolph and Hoy 1960;Olson and Dempsey 1978), support the contention of Frappell et al (1992) and others (e.g. Wood 1991), that a drop in TB and Me in response to hypoxia is a general characteristic of many species of small mammals from different mammalian orders.…”
Section: Response To Hypoxiasupporting
confidence: 84%
“…Twenty-one of 27 species from five mammalian orders included in the study by Frappell et al (1992) showed large ( > 20%) reductions in 1902 and corresponding reductions in TB upon exposure to 10% Oz. These data, together with data for five other species of rodents (Morrison and Rosenmann 1975), guinea pigs (Hill 1959), and rats (Adolph and Hoy 1960;Olson and Dempsey 1978), support the contention of Frappell et al (1992) and others (e.g. Wood 1991), that a drop in TB and Me in response to hypoxia is a general characteristic of many species of small mammals from different mammalian orders.…”
Section: Response To Hypoxiasupporting
confidence: 84%
“…Yet, as noted above, some groups of investigators have argued that the rhythmic activity of this preparation is similar to the eupnoeic pattern of the in vivo neonatal rat (Smith et al 1990Greer, Smith & Feldman, 1991;Brockhaus et al 1993). However, the rhythmic neural discharges of the in vitro preparation appear to correspond more closely to gasping, as described in adult (Adolf & Hoy, 1960;Stafford & Weatherall, 1960;Adolf, 1969). The pattern of rhythmic activity of the in vitro preparation is unalterable, except to apnoea (Suzue, 1984;Murakoshi et al 1985;Smith et al 1990Smith et al , 1991Brockhaus et al 1993;Okada, Muckenhoff & Scheid, 1993b).…”
Section: Discussionmentioning
confidence: 62%
“…However, this possibility does not appear to be consistent with the observation that, as in adults, the eupnoeic ventilatory rhythm of neonatal and fetal animals, including rats and mice, is altered to gasping upon exposure to anoxia (e.g. Adolf & Hoy, 1960;Stafford & Weatherall, 1960;Adolf, 1969;Lawson & Thach, 1977;Jacobi & Thach, 1989;Jansen & Chernick, 1991). Finally, it is possible that a single 'pre-Botzinger' complex on either side is sufficient to generate a eupnoeic rhythm.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The depth of breathing increased while respiratory rate changed little in these experiments. Yet these observations were made at an environmental temperature of 330 C or less (Adolph & Hoy, 1960) and hence may not be applicable to the present observations. The decrease in 02 consumption of new-born rats breathing low-02 mixtures could signify either inadequate uptake of 02 (in which case blood and tissue pO2 would fall and the resulting energy debt might be partially met by anaerobic glycolysis) or a decrease in blood flow to certain regions of the body.…”
Section: Discussionmentioning
confidence: 77%